THROMBOLYTIC THERAPY OF ACUTE MYOCARDIAL INFARCTION - D. P. Sementsov (Рациональная фармакотерапия в кардиологии, 2015)
Importance of thrombolytic therapy for restoration of coronary blood flow in acute myocardial infarction is emphasized. Indications and contraindications, advantages and disadvantages for thrombolysis therapy are discussed. The ways of different thrombolytics implementation, efficacy criteria and possible side effects are also presented.